The Queer Collapse of Civilization: Mariko Ōhara's "Shōjo" - Esther Andreu (Universitat de Barcelona, 2017)
This article analyses Mariko Ōhara’s short story “Shōjo” (1985) and its attempt at deconstructing the sex-gender system, focusing on the three main characters: Gil and his two sexual/love interests, Kisa and Remora. By examining the story from both gender and animal studies, the aim is to reflect on how the ideas of sex, gender and performativity are inserted into a vaster social construction that also merges with class and animality. We also consider how the recurrent image of decadence and what can be considered a return to a heteronormative situation do not undermine the overall process of deconstruction and social critique offered by the story.